Accelerated and personalized therapy for heart failure with reduced ejection fraction. (25th April 2022) - Shen, Li; Jhund, Pardeep Singh; Docherty, Kieran Francis; Vaduganathan, Muthiah; Petrie, Mark Colquhoun; Desai, Akshay Suvas; Køber, Lars; Schou, Morten; Packer, Milton; Solomon, Scott David; Zhang, Xingwei; McMurray, John Joseph Valentine
Abstract: Aims: Previously, guidelines recommended initiating therapy in patients with heart failure and reduced ejection fraction (HFrEF) in a sequence that follows the chronological order in which trials were conducted, with cautious up-titration of each treatment. It remains unclear whether this historical approach is optimal and alternative approaches may improve patient outcomes. Methods and results: The potential reductions in events that might result from (i) more rapid up-titration of therapies used in the conventional order (based on the chronology of the trials), and (ii) accelerated up-titration and using treatments in different orders than is conventional were modelled using data from six pivotal trials in HFrEF. Over the first 12 months from starting therapy, using a rapid up-titration schedule led to 23 fewer patients per 1000 patients experiencing the composite of heart failure hospitalization or cardiovascular death and seven fewer deaths from any cause. In addition to accelerating up-titration of treatments, optimized alternative ordering of the drugs used resulted in a further reduction of 24 patients experiencing the composite outcome and six fewer deaths at 12 months. The optimal alternative sequences included sodium–glucose cotransporter 2 inhibition and a mineralocorticoid receptor antagonist as the first two therapies. Conclusion: Modelling of accelerated up-titration schedule and optimized ordering of treatment suggested that at least 14 deaths and 47 patients experiencing the composite outcome per 1000 treated might be prevented over the first 12 months after starting therapy. Standard treatment guidance may not lead to the best patient outcomes in HFrEF, though these findings should be tested in clinical trials. Structured Graphical Abstract: Structural Graphical Abstract Potential reductions in events from accelerated up-titration and optimized ordering of treatment sequence compared with the conventional schedule.